Model Jaringan VLAN pada Routing IS-IS untuk Pemerintah (Studi Kasus Dinas Pemerintah Kecamatan Bringin) - Arnando, Kelvin; Widiasari, Indrastanti Ratna (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The current development of the internet network in the digital era has progressed very rapidly and has become a major need that cannot be abandoned, especially for the Bringin District Government Service which does not yet have a good network, so the exchange of information is less effective. Therefore, it is necessary to design a network with VLAN configuration on IS-IS routing, and carry out network simulation using GNS3. QoS testing is carried out by sending data packets using the ICMP protocol and counting the data sent. This research shows that the results of VLAN network testing on IS-IS routing at the Bringin District Government Service have optimal performance according to the TIPHON standard with 0% packet loss, 11.28 ms delay, 0.78 Mbit/s throughput, and 0 ms jitter.